Catalytic and ligand-binding characteristics of Plasmodium falciparum serine hydroxymethyltransferase - Pang, Cullen KT (2009)
The plant-like, bifunctional dihydrofolate reductase-thymidylate synthase (DHFR-TS) from malaria parasites has been a good target for drug development. Dihydrofolate reductase (DHFR) is inhibited by clinically established antimalarials, pyrimethamine and cycloguanil. Thymidylate synthase (TS) is the target of potent experimental antimalarials such as 5-fluoroorotate and 1843U89. Another enzyme in folate recycling, serine hydroxymethyltransferase (SHMT), produces 5,10-methylenetetrahydrofolate which, in many cells, is required for the de novo, biosynthesis of thymidine and methionine. Thus, the biochemical characterization of malarial SHMT was of interest. The principle, active P. falciparum SHMT (PfSHMT) was expressed in E. coli and purified using an N-terminal histidine tag. Unlike the plant enzyme, but like the host enzyme, PfSHMT requires the cofactor pyridoxal 5’-phosphate for enzymatic activity. The substrate specificities for serine, tetrahydrofolate, and pyridoxal 5’-phosphate were comparable to those for SHMT from other organisms. Antifolates developed for DHFR and TS inhibited SHMT in the mid-micromolar range, offering insights into the binding preferences of SHMT but clearly leaving room for improved new inhibitors. As previously seen with P. falciparum DHFR-TS, PfSHMT bound its cognate mRNA but not control RNA for actin. RNA-binding was not reversed with enzyme substrates. Unlike DHFR-TS, the SHMT RNA-protein interaction was not tight enough to inhibit translation. Another gene PF14_0534, previously proposed to code for an alternate mitochondrial SHMT, was also expressed in E. coli but found to be inactive. This protein, nor DHFR-TS, enhanced the catalytic activity of PfSHMT. The present results set the stage for developing specific, potent inhibitors of SHMT from P. falciparum.